The Effectiveness of Social-Emotional Learning (SEL) on Collaboration and Teamwork Skills among Elementary School Students - Anita Widyaningrum; Agung Hastomo; Wuri Wuryandani (Jurnal Ilmiah Sekolah Dasar, 2026)
Low levels of collaboration in elementary classrooms marked by student passivity, unequal participation, and limited social emotional engagement indicate that learning practices have tended to prioritize cognitive outcomes over essential 21st-century collaboration skills, prompting this study to empirically examine the effect of Social-Emotional Learning (SEL) on strengthening students’ teamwork abilities using a pretest–posttest control group experimental design and a collaboration skills questionnaire analyzed through descriptive statistics, normality and homogeneity tests, independent sample t-tests, and N-Gain analysis. The findings demonstrated that students in the SEL-based learning group showed significantly greater improvement in collaboration skills than those in the control group, confirming that integrating the five core SEL competencies self-awareness, self-management, social awareness, relationship skills, and responsible decision-making effectively enhanced active participation, mutual respect, and conflict resolution, thereby supporting the development of essential social-emotional competencies aligned with 21st-century learner profile.